THE EFFECT OF THE R.E.A.C.T. STRATEGY ON COGNITIVE ACHIEVEMENT AND LEARNING OF THE ROLLING AND HANDLING SKILLS OF FUTSAL FOR FEMALE STUDENTS - Assistant Professor Huda Salem Mezban (Proximus Journal Publishing, 2025)
The issue of indoor football has been the subject of recent studies and research that address the practical pedagogical aspects of contemporary instruction. In order to help the female students reach a higher level of knowledge and competence, as well as the ability to roll and handle a basic indoor football, the researcher attempted to explore this experiment utilizing a variety of media during the class. The goal was to create instructional materials based on the R.E.A.C.T. technique to help fourth-year female students in the College of Physical Education and Sports Sciences improve their cognitive abilities as well as their ability to roll and handle an indoor football
Keywords: strategy Cognitive achievement; dribbling and handling skills; indoor soccer ball